Analysis of deformation and stability characteristics of a landslide in Southwest China under different rainfall and support conditions - Zhang, Yan; Hu, Yitao; Zheng, Xiangsheng; Yu, Yang; Guo, Haosen; Gao, Meiben (Frontiers in Earth Science, 2025)
Driven by rainfall and excavation, frequent landslides in southwestern China pose a serious threat to lives and property. This study uses advanced small baselines subset-interferometric synthetic aperture radar (SBAS-InSAR) time series analysis method and Sentinel-1 satellite data, combined with numerical simulation analysis, to study the deformation and stability characteristics of the Laoyingpan Village landslide under different rainfall and support measures conditions. The study results indicate that the Laoyingpan Village landslide has a 24° average slope, covering approximately 3.8 × 105 m2 with a volume of about 1.3 × 107 m3 and an “arm-chair” shape oriented at 106°. Excavation and rainfall are key factors impacting stability, causing significant deformation, especially on the left side with translational failure. SBAS-InSAR analysis indicates a maximum subsidence rate of 25 mm/month in lower slope sections. Under extreme rainfall, the stability coefficient dropped from 1.160 to 0.871, transitioning from stable to unstable before stabilizing after 60 h due to submergence. The implementation of anti-slide piles and anchor cables improved stability, reaching a coefficient of 1.745 with optimal parameters, recommending a combined support approach for effective landslide management. The study results can provide useful reference and guidance for the stability analysis and engineering prevention of the landslides.